Do Muslim Women Need Saving? By Lila Abu-Lughod (Cambridge and London: Harvard University Press, 2013. 326 pages.) (American Journal of Islam and Society, 2015)
In this extension of her important 2002 article in American Anthropologist,Lila Abu-Lughod examines the problematic nature of the western discoursesurrounding Muslim women. In particular, she is interested in how westernpolitical programs in countries like Iraq and Afghanistan use the status ofgirls and women to validate their claims to occupy, colonize, or otherwisemeddle in Muslim countries’ internal affairs. Abu-Lughod shows how thehuman rights discourse surrounding grim situations (often aggravated orcaused by western interventions and other maneuverings) relies on a kind ofone-downtrodden-Muslim-female-fits-all scenario. This book analyzes the“idea of the Muslim woman,” a character often in need of western liberation,and argues that the lives of Muslims are more complicated and nuanced thanthe popular media would have us believe.Abu-Lughod begins her Introduction by reflecting on her fieldwork as ananthropologist in Egypt, an experience that taught her a great deal about thelives of Muslim women and has influenced her view that there is a “disjuncturebetween my experiences and these public attitudes” (p. 4). In other words, whatthe West thinks about Muslim women – their hopes, dreams, aspirations, andexperiences – is radically different than what Muslim women actually experience.These fantasies, much like the fantasies about Muslim men as irrationaland hopelessly violent, “rationalize American and European international adventuresacross the Middle East and South Asia” (p. 7). Muslim women arerepresented as lacking agency, a result in part of the alignment of sexual freedomswith personal liberation, about which Wendy Brown has written. Abu-Lughod sets off on her project to deconstruct and analyze the intersectionamong feminism, human rights language, and politics with the hope that theactual complicated, diverse, and multifaceted lives of Muslim women can contributeto a critical reflection on the growing movement for women’s rights.In chapter 1, the author sets her sights on Afghanistan, a state well knownfor its violence and poverty, not to mention the mass suffering of the generalpopulation. As she skillfully points out, the plight of Afghan girls and womenserves a foundational role in arguments for American intervention. While theTaliban certainly deserve the demonization they have received in the press,so do the numerous other factions that target women as well as religious minoritiesand ethnic groups like the Hazara. As she reminds us, some of thesegroups are in “the U.S. backed government” (p. 29) ...